2012
DOI: 10.1007/s10456-012-9323-8
|View full text |Cite
|
Sign up to set email alerts
|

The stem cell marker prominin-1/CD133 interacts with vascular endothelial growth factor and potentiates its action

Abstract: Prominin-1, a pentaspan transmembrane protein, is a unique cell surface marker commonly used to identify stem cells, including endothelial progenitor cells and cancer stem cells. However, recent studies have shown that prominin-1 expression is not restricted to stem cells but also occurs in modified forms in many mature adult human cells. Although prominin-1 has been studied extensively as a stem cell marker, its physiological function of the protein has not been elucidated. We investigated prominin-1 function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 46 publications
5
33
0
Order By: Relevance
“…For example, the loss of CD133 has been associated with reduced ductal branching in the mammary gland suggesting its importance in regulating branching morphogenesis [55]. In addition to its proposed role in branching morphogenesis, CD133 has also been shown to play an active role in cell growth through its ability to interact and potentiate the anti-apoptotic and pro-angiogenic activities of VEGF in primary human endothelial cells [56]. The differential and spatial regulation of CD133 by pre-existing vascular cells in newly forming ampullae suggests a role for CD133 in Botryllus ampullae differentiation from blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the loss of CD133 has been associated with reduced ductal branching in the mammary gland suggesting its importance in regulating branching morphogenesis [55]. In addition to its proposed role in branching morphogenesis, CD133 has also been shown to play an active role in cell growth through its ability to interact and potentiate the anti-apoptotic and pro-angiogenic activities of VEGF in primary human endothelial cells [56]. The differential and spatial regulation of CD133 by pre-existing vascular cells in newly forming ampullae suggests a role for CD133 in Botryllus ampullae differentiation from blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring these same cells in a humanized mouse model, we were able to simulate what we have observed in patients - increased pCHSPC levels correlate with tumor progression. Recently CD133, the key marker of the pCHSPC, has been shown to interact with VEGF which has pro-survival and angiogenic properties for endothelial cells and increases survival of cancer cells[24]. Further, cell growth of both endothelial and melanoma cells are also regulated through VEGF[24].…”
Section: Discussionmentioning
confidence: 99%
“…They showed that CD133 receptor directly interacts with the angiogenetic vascular endothelial growth factor which might be relevant for physiologic neovascularization but also for angiogenesis in cancer patients. In vivo angiogenesis could be inhibited by downregulation of CD133 using lentiviral short hairpin RNA sequences to silence prominin-1 gene capillary formation [ 96 ]. A study that histologically analyzed lung tissue from lung cancer patients stated that CD133 + endothelial progenitor cells contributed to neovascularization and tumor growth vascular damage was not reported after using CD133 targeted constructs but data implicate the potential of capillary complications after administration.…”
Section: Cd133 Expression On Normal Body Cellsmentioning
confidence: 99%